Bifunctional NH2-MIL-88(Fe) metal–organic framework nanooctahedra for highly sensitive detection and efficient removal of arsenate in aqueous media. Issue 45 (8th November 2017) - Xie, Donghua; Ma, Yue; Gu, Yue; Zhou, Hongjian; Zhang, Haimin; Wang, Guozhong; Zhang, Yunxia; Zhao, Huijun
Abstract : Bifunctional NH2 -MIL-88(Fe) nanooctahedra have been successfully fabricated for highly sensitive and specific recognition as well as efficient removal of arsenate. Abstract : Extensive exposure to and high toxicity of arsenic species have posed severe health threats worldwide. Consequently, it is imperative to develop novel dual functional materials, which can not only precisely monitor trace levels of arsenic, but also simultaneously realize its efficient decontamination. In this study, amino-functionalized iron-based metal organic framework (MOF) nanooctahedra have been successfully synthesized via a facile one-step solvothermal route for the selective detection and facile removal of arsenate from polluted water. Benefiting from the unique fluorescence enhancement and high specific surface area as well as excellent stability, the resultant NH2 -MIL-88(Fe) nanooctahedra can be utilized for the quantitative assay of arsenate, accompanied by a fast response time (<1 min), broad linear range (0.1–50 μM) and high sensitivity (detection limit of as low as 4.2 ppb) along with excellent selectivity towards arsenate. More significantly, the proposed sensing system has been further exemplified for the determination of arsenate in real environmental water samples with acceptable recoveries, highlighting its feasibility in complicated environmental samples. It is noteworthy that the as-synthesized NH2 -MIL-88(Fe) nanooctahedra also exhibit extraordinary sorption performance towards As(v ) in terms of high saturated adsorption capacity (125 mg g −1 ) and fast sorption kinetics, capable of easily reducing trace amounts of As(v ) to below the acceptable standard for drinking water within 60 min. These results indicate that the obtained NH2 -MIL-88(Fe) nanooctahedra can be expected to be an excellent candidate for arsenic determination and remediation from contaminated water systems.